Structural reform: The experience of ten schools driving the development of an all-age hard federation across a market town in northern England. (January 2015) - Howland, Gill
This article provides a narrative which illustrates the experiences of one group of UK schools as they have attempted to introduce innovation in order to achieve their collective vision of improving educational opportunity for all pupils in their care. It considers the findings of a small-scale research project which follows, over a 3-year period, the proposed development of an all-age hard federation of ten schools, the vision and plans for which were conceived and developed by the schools' leaders. The article considers the factors that have enabled or constrained the collaboration of the schools, and focuses on the evolution of the schools' initial proposal in response to the changing requirements of central government. The article ends with a reflection upon the purposes, intentions and roles of each of the key players, and concludes that, in an era of freedoms and flexibilities, unintentional blockages and forces are at play that serve to undermine the policy intention.